ECONOMY AND ENVIRONMENT OF THE GREEK COLONIAL SYSTEM IN SOUTHERN ITALY: POLLEN AND NPPS EVIDENCE OF GRAZING FROM THE RURAL SITE OF FATTORIA FABRIZIO (VI-IV CENT. BC; METAPONTO, BASILICATA) - Florenzano, A.; Mercuri, A.M.; Carter, J.C. (Annali di Botanica, 2013)
This paper reports a study case showing integrated analyses of microscopic records from an archaeological site of southern Italy. Pollen and non pollen palynomorphs-NPPs were found in archaeological layers and were basic in reconstructing both the past environment and the economic activities of the site. The site, Fattoria Fabrizio, is a modest 4th-cenury BC farmhouse of the chora (rural territory) of the Greek city (polis) of Metaponto (Basilicata). Pollen analyses in addition to the study of NPPs have been particularly worthwhile for palaeoenvironmental and palaeoeconomical reconstructions of this site and others in the chora. The pollen spectra delineate an open plant landscape, with scanty woodlands and presence of local wet environments. Olea pollen is fairly well represented in all samples, suggesting that this tree was an important element of the agricultural economy of the chora. Shrubby grasslands and a well-developed maquis characterized the territory, probably as result of grazing activities by sheep and goats. Accordingly, the high percentages of Poaceae and Cichorieae pollen, together with coprophilous fungal spores (such as Sordaria type and Sporormiella type), suggest that pastoral activities were widely practiced. The low number of Cerealia pollen grains suggests that the inhabitants’ fields covered small areas or were quite far from the farmhouse.